Amphetamine-type stimulant (ATS) use and association with concurrent use of benzodiazepines, barbiturates and THC in the West Bank among male Palestinians: a cross-sectional study - Basma Damiri; Adnan Mousa; Maroun Amin Helou (BMJ Publishing Group, 2023)
Introduction Amphetamine-type stimulants (ATSs) are becoming a growing concern in the West Bank. Despite the focus on marijuana, statistics show that ATS seizures and clandestine laboratories indicate increased use of this highly addictive chemical among Palestinians. Shifting from marijuana to ATS can have severe clinical and social consequences, yet insufficient studies have been conducted. Our study aimed to evaluate the prevalence of ATS use and its correlation with other drug use in male Palestinians living in the northern West Bank.Methods A cross-sectional study was conducted among Palestinian men aged ≥18 years from the north of the West Bank in 2022-2023. A self-administered questionnaire and urine analysis test were used to determine drug use. ATS users in this study tested positive for at least one of the following: amphetamines, ecstasy or methamphetamines.Results Out of 787 participants, 129 (16.4%) were drug users. The prevalence of drug use among drug users was as follows: benzodiazepines (55.8%), amphetamines (41.1%), tetrahydrocannabinol (THC) (38.8%), methamphetamines (38.0%), barbiturates (9.3%), phencyclidine (1.6%) and ATS (48.8%); 84.1% were amphetamine and 77.7% were methamphetamine users. Most ATS users (68.3%) were polydrug users; 57.1% were benzodiazepine, 30.2% were THC and 12.7% were barbiturate users. The adjusted binary logistic regression revealed that ATS users were more likely to be benzodiazepine (OR=11.059, p<0.001), THC (OR=5.520, p<0.001) and barbiturate users (OR=17.109, p=0.01).Conclusion The study found that ATS use is widespread among Palestinian men and is associated with other drug use, including benzodiazepines, barbiturates and THC. The study recommends implementing better strategies and policies for controlling and confiscating illicit substances to address the severe medical and sociological problems that can arise from drug dependence. Additionally, the study highlights the risks associated with transitioning from marijuana to ATS, which can have severe clinical and social consequences.